Use of transesophageal echocardiography guidance for pulmonary artery banding in a cat with ventricular septal defect - D.N. Acosta; S. Sudunagunta; S. Swift; S. Goodrich; A. Mathis; W. Robinson; F. Sarcinella (Journal of Veterinary Cardiology, 2026)

KPC-producing Klebsiella pneumoniae in Switzerland from 2024 to 2025: comparative genomics and cefiderocol resistance mechanisms analyses - Jacqueline Findlay; Patrice Nordmann; R Lienhard; L Vonallmen; C Schilt; A Scherler; K Lucke; M Jutzi; M Reichmuth; U Schibli; C Fricker; S Pranghofer; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

In vitro activity of β-lactamase inhibitors avibactam, relebactam and vaborbactam in combination with aztreonam against metallo-β-lactamase producing Escherichia coli clinical isolates - Clément Viguier; Samanta Freire; Maxime Bouvier; Christophe Le Terrier; Laurent Poirel; A. Westers; M. Imperiali; L. Pozzi; D. Balzari; G. Vaninetti; C. Cirillo; V. Gaia; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Combined resistance mechanisms leading to high-level of cefiderocol resistance among NDM-like producing E. coli ST167 clinical isolates - Mustafa Sadek; Juan Bosch Duran; Trinad Chakraborty; Laurent Poirel; R. Lienhard; L. Vonallmen; C. Schilt; A. Scherler; K. Lucke; M. Jutzi; M. Reichmuth; V. Slutter; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Summary Purpose A series of NDM-producing Escherichia coli ST167 clinical isolates exhibiting resistance to cefiderocol (FDC), with no previous exposure to this antibiotic, were analyzed in this study. Methods The antimicrobial susceptibility testing and phenotypic detection of resistance patterns (Rapid Cefiderocol NP test and MIC determination) were performed for all tested isolates. Their entire genomes were sequenced by using the Illumina MiSeq platform and high-quality reads were de-novo assembled using the CLC Genomic Workbench. Genome-sequence based characteristics were analyzed using bioinformatics tools. Results All NDM-producing E. coli ST167 isolates showed a high level of resistance to FDC (MICs being 64 or > 64 mg/L). The chromosomally located cirA gene, encoding a catecholate siderophore receptor in E. coli , was truncated in all FDC-resistant isolates due to a frameshift mutation (S90Y), leading to CirA-deficient isolates. A four amino acid insertion (YRIN) was also identified after residue 333 in the PBP3 protein sequence of all E. coli isolates. Among them, a single FDC-resistant NDM-5-producing E. coli isolate (1006) was additionally resistant to aztreonam/avibactam (AZA MIC of 8 mg/L). When analyzed against the genome of another FDC resistant NDM-5 producing E. coli ST167 containing a YRIN insertion in the PBP3, and exhibiting decreased susceptibility to AZA, the broad-spectrum ß-lactamase CMY-42 was identified. Conclusion We identified a variety of NDM-producing E. coli isolates exhibiting high level of resistance to FDC as a result of the combined effect of CirA deficiency, along with production of NDM-type enzymes. The spread of such resistance phenotype across Europe poses great concern on the clinical efficacy of this novel drug. Additionally, the identification of an FDC- and AZA-resistant NDM-5 producing E. coli isolate represents one of the ultimate evolutions with a possible step towards pan-resistance.

P02-25 Use of organotypic gingival cultures for nicotine pouch assessment - F. Zanetti; M. Alriquet; L. Ortega Torres; L. Neau; F. Maranzano; C. Pak; C. Mathis (Toxicology Letters, 2024)

Molecular analysis of metallo-beta-lactamase-producing Pseudomonas aeruginosa in Switzerland 2022–2023 - Jacqueline Findlay; Otavio Hallal Ferreira Raro; Laurent Poirel; Patrice Nordmann; R. Lienhard; L. Vonallmen; C. Schilt; A. Scherler; K. Lucke; M. Jutzi; M. Reichmuth; U. Schibli; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Objectives The occurrence of metallo-beta-lactamase-producing Pseudomonas aeruginosa (MBL-PA) isolates is increasing globally, including in Switzerland. The aim of this study was to characterise, phenotypically and genotypically, the MBL-PA isolates submitted to the Swiss National Reference Center for Emerging Antibiotic Resistance (NARA) reference laboratory over a 12-month period from July 2022 to July 2023. Methods Thirty-nine non-duplicate MBL-PA Isolates were submitted to NARA over the study period from across Switzerland. Susceptibility was determined by broth microdilution according to EUCAST methodology. Whole-genome sequencing was performed on 34 isolates. Sequence types (STs) and resistance genes were ascertained using the Centre for Genomic Epidemiology platform. MBL genes, bla NDM-1 , bla IMP-1 , and bla VIM-2 , were cloned into vector pUCP24 and transformed into P. aeruginosa PA14. Results The most prevalent MBL types identified in this study were VIM (21/39; 53.8%) followed by NDM (11/39; 28.2%), IMP (6/39; 15.4%), and a single isolate produced both VIM and NDM enzymes. WGS identified 13 different STs types among the 39 isolates. They all exhibited resistance to cephalosporins, carbapenems, and the beta-lactam-beta-lactamase inhibitor combinations, ceftolozane-tazobactam, ceftazidime-avibactam, imipenem-relebactam, and meropenem-vaborbactam, and 8 isolates were cefiderocol (FDC) resistant. Recombinant P. aeruginosa strains producing bla NDM-1 , bla IMP-1 , and bla VIM-2 exhibited FDC MICs of 16, 8, and 1 mg/L, respectively. Conclusions This study showed that the MBL-PA in Switzerland could be attributed to the wide dissemination of high-risk clones that accounted for most isolates in this study. Although FDC resistance was only found in 8 isolates, MBL carriage was shown to be a major contributor to this phenotype.

Bayesian QTL analyses using pedigreed families of an outcrossing species, with application to fruit firmness in apple - M. C. A. M. Bink; J. Jansen; M. Madduri; R. E. Voorrips; C.-E. Durel; A. B. Kouassi; F. Laurens; F. Mathis; C. Gessler; D. Gobbin; F. Rezzonico; A. Patocchi; et al. (Theoretical and Applied Genetics, 2014)

Parasite Lost: Chemical and Visual Cues Used by Pseudacteon in Search of Azteca instabilis - Kaitlyn A. Mathis; Stacy M. Philpott; Rayane F. Moreira (Journal of Insect Behavior, 2011)

Development and test of 21 multiplex PCRs composed of SSRs spanning most of the apple genome - A. Patocchi; F. Fernández-Fernández; K. Evans; D. Gobbin; F. Rezzonico; A. Boudichevskaia; F. Dunemann; M. Stankiewicz-Kosyl; F. Mathis-Jeanneteau; C. E. Durel; L. Gianfranceschi; F. Costa; et al. (Tree Genetics & Genomes, 2009)

Serotonin transporter binding after recovery from eating disorders - Ursula F. Bailer; Guido K. Frank; Shannan E. Henry; Julie C. Price; Carolyn C. Meltzer; Carl Becker; Scott K. Ziolko; Chester A. Mathis; Angela Wagner; Nicole C. Barbarich-Marsteller; Karen Putnam; Walter H. Kaye (Psychopharmacology, 2007)

Effect of adenoviral mediated overexpression of fibromodulin on human dermal fibroblasts and scar formation in full-thickness incisional wounds - Alexander Stoff; Angel A. Rivera; J. Michael Mathis; Steven T. Moore; N. S. Banerjee; Maaike Everts; Antonio Espinosa-de-los-Monteros; Zdenek Novak; Luis O. Vasconez; Thomas R. Broker; Dirk F. Richter; Dale Feldman; et al. (Journal of Molecular Medicine, 2007)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)